2016
DOI: 10.4014/jmb.1511.11046
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antibacterial Effect and Antibacterial Action Mode of Chitosan-Ferulic Acid Conjugate against Methicillin-Resistant Staphylococcus aureus

Abstract: The object of this study was to discover an alternative therapeutic agent with fewer side effects against acne vulgaris, which is one of the most common skin diseases. Acne vulgaris often associates with acne-related bacteria such as Propionibacterium acnes, Staphylococcus epidermidis, Staphylococcus aureus and Pseudomonas aeruginosa, some of which exhibit a resistant against commercial antibiotics used in the treatment of acne vulgaris (tetracycline, erythromycin, and lincomycin). In the current study, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 0 publications
7
27
0
Order By: Relevance
“…These results were also accordance with the report by Eom et al [12] that chitosan-derived conjugates clearly reversed antibacterial activity of β-lactam antibiotics against methicillin-resistant S. aureus (MRSA) in the combination mode. The median ΣFIC indices were in the ranges of 0.375 to 0.563.…”
Section: Synergistic Antibacterial Effect Between Cca and Antibioticssupporting
confidence: 83%
See 4 more Smart Citations
“…These results were also accordance with the report by Eom et al [12] that chitosan-derived conjugates clearly reversed antibacterial activity of β-lactam antibiotics against methicillin-resistant S. aureus (MRSA) in the combination mode. The median ΣFIC indices were in the ranges of 0.375 to 0.563.…”
Section: Synergistic Antibacterial Effect Between Cca and Antibioticssupporting
confidence: 83%
“…It has been demonstrated that one of the more effective strategies in developing new drugs or alternative therapies is the restoration of antibiotic activity in combination with antibacterial materials derived from natural products and traditional medicines against drugresistant bacteria [12,[30][31][32]. Based on these reports, an interaction between chitosan-phytochemicals and commercial antibiotics were estimated by the checkerboard method as stated above and the results were presented in Table 3.…”
Section: Synergistic Antibacterial Effect Between Cca and Antibioticsmentioning
confidence: 99%
See 3 more Smart Citations